Motivations to visit and image destination of Guimarães: differences between Portuguese and foreign tourists during 2012 Guimarães European Capital of Culture (ECOC) - Freitas Santos, José (2013)
Guimarães hosted the European Capital of Culture (ECOC) during the year of 2012. This study investigates the differences between Portuguese and foreign tourists regarding the main motivations to visit Guimarães and the retained perceived image of the destination. To achieve that purpose a survey was administered to 390 tourists that visited the city during the cultural event. The results show that tourists who visited Guimarães are relatively young, wealthy, employed and well educated. They are touring around the northern part of the country which includes an itinerary beginning in Porto, and extended to other important neighboring cities such as Braga or Viana do Castelo. The main motivations to visit the city, for both Portuguese and foreign tourists, are its historical heritage and the title of ECOC, the associated cultural events and celebrations that take place during 2012. However, these items were more valued by foreigners than Portuguese tourists. Using a factor analysis the tourists’ perceived attributes of Guimarães were described in four dimensions: “material heritage”, “intangible heritage”, “cultural performance”, and “sport and education”. Although foreigners and nationals perceived the tourism attributes of the city differently, the comparison of the mean scores of the four factors across Portuguese and foreigner tourists reveals that the most valued and least valued factors are common to both groups.